Analysis of ROA, ROE, CR, and Der on Stock Return of Non-Banking Companies in LQ-45 Index in Indonesia Stock Exchange 2015-2019 - Santoso, Herry; Owen, Keane; Raissa, Zabrina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study has a main purpose to analyze and assess empirically financial ratios consisting of Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) and its Impact on Stock Return. Secondary data will be used for this research. Purposive sampling will be used to choose the sample needed to be analyzed with the purpose of obtaining the right sample criteria. The sample for this study is non-banking companies registered in LQ-45 Index in Indonesian Stock Exchange from the year 2015 to 2019 which consists of 39 companies. Multiple linear regression is chosen as the model to be used in this research to analyze the obtained data. The result of study indicated that ROA has positive influences on stock return, but CR has negative influences. While for ROE and DER, those have no influence on stock returns.